2019
DOI: 10.3390/socsci8020064
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Children, Blaming Parents: Frontline Providers’ Perception of Childhood’s Adversity and Parenthood in Indonesia

Abstract: This article explores the construction of childhood and parenthood in rural communities in Indonesia based on a series of focus group discussions with service providers, community decision makers, and paraprofessionals; a group that we refer to as “frontline providers”. By examining the providers’ definition of successful children and their perception of factors that could undermine a child’s success, we provide insights into how frontline providers understand the role of parents, and how parenthood is constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…For example, a singular focus on ending child beating and violence in the family can make local parents feel disrespected since the intent behind corporal punishment is to enable children to grow up with good behavior and values. Worse yet, this deficits approach blames parents for harms to children, when the parents had been trying to do the right thing (Siagian, Arifiani, Amanda, & Kusumaningrum, 2019). Disrespect and blame are weak starting points for NGOs or Government stakeholders to make progress in helping to end family violence.…”
Section: Lack Of Comprehensivenessmentioning
confidence: 99%
“…For example, a singular focus on ending child beating and violence in the family can make local parents feel disrespected since the intent behind corporal punishment is to enable children to grow up with good behavior and values. Worse yet, this deficits approach blames parents for harms to children, when the parents had been trying to do the right thing (Siagian, Arifiani, Amanda, & Kusumaningrum, 2019). Disrespect and blame are weak starting points for NGOs or Government stakeholders to make progress in helping to end family violence.…”
Section: Lack Of Comprehensivenessmentioning
confidence: 99%
“…A new generation of scholars from the global South is continuing this work (e.g., Ejuu, 2015; Ng'asike and Swadener, 2019; Oppong, 2015; Rai, 2019). Other researchers apply sociological approaches to global ECD, focusing mainly on the social construction and circulation of a particular, Western‐derived concept of childhood through this movement (Nilsen and Steen‐Johnsen, 2020; Penn, 2011; Siagian et al., 2019). Some critical responses to global ECD are also emerging from various medical fields: a group of psychiatrists and medical anthropologists in South Africa recently pointed out the need to consider local knowledge in infant mental health, an applied field that largely overlaps with ECD (Lachman et al., 2021).…”
Section: Toward a Critical Engagement With Global Ecdmentioning
confidence: 99%
“…Some research exemplars come to mind, including the Peterman et al (2017) article cited above that demonstrated the potential of cash transfer programs to simultaneously reduce poverty and violence against children. In a less hopeful example, in their analysis of parenting programs in Indonesia, Siagian et al (2019) embedded their analysis in neoliberal policies and forces, finding that, by individuating parents primarily as agents of a productive economy, parenting programs ultimately blamed parents and undermined their ability to care for their children. In yet another hypothetical case, we could also suggest that measurement of efforts to reduce school-based violence must also go hand in hand with measurement of children's access to quality education.…”
Section: Broaden Analytical Models For Evaluationmentioning
confidence: 99%